Non-target metabolomic analysis reveals the therapeutic effect of Saposhnikovia divaricata decoction on collagen-induced arthritis rats. (10th May 2021) - Li, Yueyue; Lv, Diya; Liu, Rong; Shi, Yuhuan; Wang, Rong; Zhu, Zhenyu; Yuan, Yongfang
Abstract: Ethnopharmacological relevance: Saposhnikovia divaricata (SD), a Chinese crude drug, has long been recognized for therapeutic effect to rheumatoid arthritis (RA). At present, the mechanisms of SD treatment in RA have not been fully understood especially on the perspective of metabolomics. Aim of the study : To study the pharmacodynamic effects of Saposhnikovia divaricata decoction on CIA rats, and explore the therapeutic mechanism by metabolomics methods. Materials and methods: Wistar rats were randomly divided into normal group, CIA model group, dexamethasone group and SD decoction groups (10 g crude drug/kg, 5 g crude drug/kg and 2.5 g crude drug/kg of SDD). Body weight, arthritis scores, serum cytokine levels and histopathological parameters of rats were assessed. A metabolomics method based on ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOFMS) was established to collect the metabolic profiles of rats and explore the metabolic changes that occurred after SDD treatment. Results: SDD showed its protective effect on the affected joints, especially in the middle dosage group of SDD. Eighteen and 13 potential biomarkers for the SDD treatment of CIA rats were identified in the plasma and urine, respectively. SDD could regulate the disturbed metabolic pathways including tryptophan metabolism, glycerophospholipid catabolism, primary bile acid biosynthesis and fatty acid metabolism. Conclusions: In summary, SDD treatment could effectively alleviate symptoms of RA and regulate metabolic disorders in CIA rats. Graphical abstract: Image 1 Highlights: Saposhnikovia divaricata decoction could effectively alleviate symptoms of CIA rats. Differentially biomarkers were identified for the SDD treatment of CIA. Saposhnikovia divaricata decoction could regulate the disturbed metabolic pathways.